Univariate statistics and metabolomics - Wehrens, Ron (Henry Stewart Talks, 2017)
Statistics: an important part of metabolomics experiments, Sources of variation, Design of Experiments, Data visualization, Statistical testing, Linear models
Reviewed at 2023/07/06